Kemampuan Menulis Teks Pidato Dengan Menggunakan Media Audiovisual Peserta Didik Kelas X SMA Swasta Plus Setia Kabupaten Kepulauan Mentawai - Yusmiar; Eva Fitrianti; Dwi Muthia Chan (Kilau Publishing, 2023)
This study was motivated by students’ low ability to write speech texts in Indonesian language learning. The research problem was formulated as follows: how capable are Grade 10 students of SMA Swasta Plus Setia, Kepulauan Mentawai Regency, in writing speech texts using audiovisual media? Accordingly, the study aimed to describe students’ ability to write speech texts with the support of audiovisual media. The research employed a quantitative approach with a descriptive method. The sample was selected using purposive sampling. The research data consisted of test scores from students’ speech-text writing using audiovisual media. Data analysis followed these steps: (1) reviewing students’ written work, (2) determining writing scores based on an assessment rubric, (3) recording scores and converting them into grades, (4) calculating the mean score for each assessment aspect, (5) describing students’ writing ability using a ten-point scale, (6) discussing the analysis results and presenting a histogram of overall speech-writing ability, and (7) drawing conclusions. The results showed that the mean score for the opening component was 86.67, for the content component was 70.00, and for the closing component was 74.44. Overall, students’ ability to write speech texts using audiovisual media was categorized as very good, with an average score of 77.03.